A Potential Parameter for A Non-Darcy Form of Two-Phase Flow Behaviour, Compressibility Related - Busahmin, Bashir; Maini, Brij (International Journal of Engineering and Technology, 2018)
Numerous scientists did their studies and conducted various laboratory experiments related to a non-Darcy behavior of a two-phase flow for the past thirty years, and made an effort to clarify the behavior. Non-Darcy flow behavior, phenomena occurred in primary recovery method of reservoirs that have an API degree gravity of less than 20. It was confirmed that it results in greater production. The compressibility of foam fits to be the one of the general fundamental factor that directs the lifetime of a non-Darcy form of two phase flow behavior or also is known as the foamy oil.  In the process of usual drive depletion, foamy oil featured of low production GOR and high daily production rate. Foamy oil is more compressible than conventional solution gas due to the oil that gas dispersed in it; as a result, oil formation volume factor is much higher than that in conventional oil. This paper represents a laboratory data followed by some of the analysis related to the properties of non-Darcy form of two phase flow and that is the compressibility parameter. The experimental results showed that at different saturation pressures and at a room temperature, the trends fit the expected behavior above the saturation pressures. Moreover, the measurements of live oil compressibility were also attempted below the saturation pressures. It was concluded that other properties such as the viscosity is added a significant effect rather than compressibility in the behavior of what so called  foamy oil compared to the presence or absence of asphaltenes and other polar oil components.